1998
DOI: 10.4315/0362-028x-61.7.823
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Water Wash, Trimming, and Combined Hot Water and Lactic Acid Treatments for Reducing Bacteria of Fecal Origin on Beef Carcasses

Abstract: Cleaning treatments, such as high-pressure water wash at 35 degrees C or trim, alone and combined with sanitizing treatments, such as hot water (95 degrees C at the source), warm (55 degrees C) 2% lactic acid spray, and combinations of these two sanitizing methods, were compared for their effectiveness in reducing inoculated numbers (5.0 to 6.0 log CFU/cm2) of Salmonella typhimurium, Escherichia coli O157:H7, aerobic plate counts, Enterobacteriaceae, total coliforms, thermotolerant coliforms, and generic E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(39 citation statements)
references
References 0 publications
0
35
1
3
Order By: Relevance
“…Bosilevac et al (2006) reported that the bacterial count for E. coli was 3 log 10 CFU/100 cm 2 in response to the spraying of 2% lactic acid on carcass tissue, a reduction of 1.0 log CFU/100 cm 2 compared to the control group. However, the results reported here show that the efficacy of 1-3% lactic acid in reducing E. coli was lower than in this previous study; 2% lactic acid reduced E. coli numbers by 0.1 log 10 CFU/g in sheep meat at 96 h. In some studies in which inocula were experimentally added to meat samples (Castillo et al 1998(Castillo et al , 1999(Castillo et al , 2001, colony counts showed large reductions of greater than 4 log 10 CFU/g. Similar to this study, levels were reduced to less than 1 log 10 CFU/g when natural contaminants were evaluated (Dormedy et al 2000;Gill & Badoni 2004).…”
Section: Food Technology and Economy Engineering And Physical Propercontrasting
confidence: 39%
“…Bosilevac et al (2006) reported that the bacterial count for E. coli was 3 log 10 CFU/100 cm 2 in response to the spraying of 2% lactic acid on carcass tissue, a reduction of 1.0 log CFU/100 cm 2 compared to the control group. However, the results reported here show that the efficacy of 1-3% lactic acid in reducing E. coli was lower than in this previous study; 2% lactic acid reduced E. coli numbers by 0.1 log 10 CFU/g in sheep meat at 96 h. In some studies in which inocula were experimentally added to meat samples (Castillo et al 1998(Castillo et al , 1999(Castillo et al , 2001, colony counts showed large reductions of greater than 4 log 10 CFU/g. Similar to this study, levels were reduced to less than 1 log 10 CFU/g when natural contaminants were evaluated (Dormedy et al 2000;Gill & Badoni 2004).…”
Section: Food Technology and Economy Engineering And Physical Propercontrasting
confidence: 39%
“…For valid comparisons to be made, two different sets of data based on the inoculum used must be distinguished. In one set of studies, large reductions of greater than 4 log CFU (APC, Salmonella Typhimurium, E. coli O157:H7, and coliforms) were found when laboratory strains were used to inoculate beef surfaces (10,12,13). In the other set of studies, smaller reductions of 0.8 to 1.2 log CFU were found when natural contamination was evaluated (15,22).…”
Section: Resultsmentioning
confidence: 93%
“…Lactic acid has been described as an effective intervention on cold or chilled beef carcasses (13,18,22) and on hot beef carcasses (10,12,15), even though these surfaces can be very different. In those studies, the concentration of lactic acid was either 2 or 4% and the application temperatures were approximately 32ЊC (90ЊF) or 55ЊC (131ЊF).…”
Section: Resultsmentioning
confidence: 99%
“…Practices to prevent or reduce E. coli O157:H7 contamination of beef carcasses are primarily applied at the processing level, with the most common treatments being hide washes, trimming of contaminated carcass parts, steam vacuuming, hot water and acid washes, and steam treatment (1,2,4,5). Despite the implementation of these practices, there continue to be significant numbers of recalls and beef-linked illness caused by this pathogen.…”
mentioning
confidence: 99%